Trials Methodology Research: what is it and why should India invest in it? - Sangeetha Paramasivan; Anant Bhan; Rashmi Rodrigues; Usha Menon (Elsevier, 2024)
Summary: This Viewpoint presents an overview of trials methodology research (TMR) and the case for investing in TMR in India. Randomised controlled trials and other types of clinical research inform evidence-based medicine, but this endeavour is dependent on the quality of such research. TMR is aimed at improving the way in which clinical trials are designed, conducted, analysed, and reported. The evolution of TMR in countries like the UK has been nurtured through dedicated funding support. Similar funding opportunities for TMR in India will help optimise the ethical and methodological rigour of the growing number of trials conducted in India. Such funding could help initiate an interdisciplinary network of key stakeholders in India to lead on TMR priority-setting exercises so that methodological questions of relevance to India are addressed. The establishment of trials methodology hubs will enhance initiatives such as the disease-specific clinical trials networks being set up as part of the National Biopharma Mission in India. We posit that promoting and establishing TMR as a distinct field of study in India will ensure the improvement of our health research ecosystem and call on national and international funding bodies to initiate consultation, consensus building and ringfenced funding for TMR in India.